Mothers' Perspectives on learning through Play in the Home. Issue 1 (March 2016) - Colliver, Yeshe
RESEARCH IN THE FIELD of early childhood education and care (ECEC) indicates that if educators can align their perspectives and practices with families' perspectives, children's educational outcomes will improve. Yet the literature reveals educators focus on children's independent learning of various developmental domains, while mothers increasingly focus on adult-guided learning of curricula in preparation for school. To illuminate potential ways for educators to align these divergent perspectives, this paper reports on a qualitative case study of eight mothers' perspectives on their children's learning through play in the home. It revealed emphases on children's independent learning of family practices through play, contrasting starkly with previous accounts of mothers being focused on adults guiding play to cognitive learning (e.g. literacy, numeracy). Thus another perspective divergence emerged: between mothers' perspectives in the home and ECEC settings. However, the similarity between educators' perspectives to those of mothers suggests ways forward.